HR+/HER2- de novo metastatic breast cancer: a true peculiar entity? - Rosalba Torrisi; Flavia Jacobs; Chiara Miggiano; Rita De Sanctis; Armando Santoro (BioExcel Publishing Ltd, 2023)
De novo metastatic breast cancer (dnMBC) accounts for ~6-10% of all breast cancers and for ~30% of MBC with increasing incidence over time. Hormone receptor-positive/human epidermal growth factor receptor 2-negative (HR+/HER2-) tumours are the most frequent subtype with a similar incidence to that observed amongst recurrent MBC (rMBC). Higher frequency of PI3KCA and ARID2 mutations and a lower frequency of ESR1 mutations and of genes involved in DNA damage, as compared with rMBC, have been reported in HR+/HER2- dnMBC; however, these are not correlating with prognosis, whilst tumour mutational burden is inversely correlated with outcome. Bone represents the most frequent metastatic site, being the single site in up to 60% of patients with dnMBC. HR+/HER2- dnMBC has been generally reported to have better outcomes than rMBC, with a median overall survival ranging from 26 months to nearly 5 years in patients with favourable features such as age <40 years and bone-only disease, but not when compared with patients with late recurring disease (≥2-5 years). Analyses of the de novo cohorts within randomized clinical trials and large real-world series report a better outcome after treatment with CDK4/6 inhibitors and endocrine agents as compared to rMBC. Despite the limitations of retrospective studies and controversial results of the randomized trials, locoregional treatment of the primary tumour after response to systemic therapy appears to confer a survival benefit, particularly in patients with favourable prognostic factors. Altogether genomic, biological and clinical findings highlight HR+/HER2- dnMBC as a peculiar entity as compared with rMBC and deserve a dedicated treatment algorithm. This article is part of the Tackling clinical complexity in breast cancer Special Issue: https://www.drugsincontext.com/special_issues/tackling-clinical-complexity-in-breast-cancer/